Analisis Prioritas Kritis Berbasis Prinsip Pareto dalam Tata Kelola Sumber Daya Penelitian: Strategi Peningkatan Efisiensi dan Efektivitas Riset di STIE Ganesha - M. Tafsiruddin; Zulkifli Zainuddin; Rasmawati A.R; Rahman Nurhakim; Aep Saefullah (Yayasan Literasi Sains Indonesia, 2025)
This study aims to identify the dominant factors affecting the efficiency and effectiveness of research activities at STIE Ganesha through the application of the Pareto Principle. Variations in research performance among teams, particularly in terms of outputs, timeliness, and resource utilization, serve as the foundation for this analysis. A descriptive quantitative method was employed, involving lecturers participating in research and community service grants during 2024–2025. Data were collected through Likert-scale questionnaires, structured interviews, and documentation reviews. The findings reveal that limited research facilities and inefficient use of funds account for 79.6% of research obstacles, while other factors—including team collaboration, time management, institutional support, and research outputs—contribute minimally. These results highlight the need for strategic prioritization in strengthening research infrastructure, improving financial efficiency, and implementing evidence-based research management. The Pareto Principle proves to be an effective decision-making tool for optimizing research resources and developing more targeted and sustainable institutional research policies.